Study on knowledge, attitude and behaviour of patient towards dermatophytosis and importance of maintaining personal hygiene - S., Sivaramakrishnan Sangaiah; S., Arun Karthikeyan; N., Ashok Kumar; G., Sukanya (International Journal of Advances in Medicine, 2021)
Background: Dermatophytosis is considered as a silent epidemic with a global prevalence of 25%. In India, it has been reported in various studies with high prevalence of 27% and it is important to find the modifiable contributing factors for dermatophytosis, so as to prevent the high morbidity affecting the social and occupational health. Methods: A total of 100 patients participated in this cross-sectional study conducted in dermatology outpatient department (OPD) at tertiary care hospital. After obtaining informed written consent, all patients above 18 years of age diagnosed with superficial fungal Skin infections were subjected to pretested, semi-structured questionnaire to collect data regarding the knowledge, attitude and practices towards the dermatophytosis. Results: Out of 100 patients in this study, 45% of patients has knowledge about the spread of fungal infection from person to person and 55% patients not agreeing with it. The study also revealed that 84% of patients reported correctly about the association of sweating with sweat feeling index (SFI) and 76% of patients know about the possible sites of dermatophyte infection. 91% and 96% of patients had no knowledge about the spread of infection through sharing clothes and collective washing clothes of other family members. Conclusions: Despite the patients demonstrating good knowledge about mode of spread of dermatophytosis, still most of the patients are failed to implement the knowledge in maintaining personal hygiene practices. There is a need to improve the gap between the knowledge about the dermatophytosis and their personal hygiene practices towards the infection. It is important to communicate with the patient about the treatment of other family members and changing their attitude towards the infection. This approach will help to improve the adherence of treatment and also prevents the recurrence of dermatophytosis.